The energetic brain – A review from students to students. Issue 2 (10th September 2019) - Bordone, Melina Paula; Salman, Mootaz M.; Titus, Haley E.; Amini, Elham; Andersen, Jens V.; Chakraborti, Barnali; Diuba, Artem V.; Dubouskaya, Tatsiana G.; Ehrke, Eric; Espindola de Freitas, Andiara; Braga de Freitas, Guilherme; Gonçalves, Rafaella A.; et al.
Abstract: The past 20 years have resulted in unprecedented progress in understanding brain energy metabolism and its role in health and disease. In this review, which was initiated at the 14th International Society for Neurochemistry Advanced School, we address the basic concepts of brain energy metabolism and approach the question of why the brain has high energy expenditure. Our review illustrates that the vertebrate brain has a high need for energy because of the high number of neurons and the need to maintain a delicate interplay between energy metabolism, neurotransmission, and plasticity. Disturbances to the energetic balance, to mitochondria quality control or to glia–neuron metabolic interaction may lead to brain circuit malfunction or even severe disorders of the CNS. We cover neuronal energy consumption in neural transmission and basic ('housekeeping') cellular processes. Additionally, we describe the most common (glucose) and alternative sources of energy namely glutamate, lactate, ketone bodies, and medium chain fatty acids. We discuss the multifaceted role of non‐neuronal cells in the transport of energy substrates from circulation (pericytes and astrocytes) and in the supply (astrocytes and microglia) and usage of different energy fuels. Finally, we address pathological consequences of disrupted energy homeostasis in the CNS. Abstract : Why does the brain need so much energy, and what is known about the energetic costs of neural transmission? In this review, we address the basic concepts of brain energy metabolism and its delicate interplay with neurotransmission and plasticity. Disturbances to the energetic balance, to mitochondria quality control or to glia–neuron metabolic interaction may lead to brain circuit malfunction or even severe disorders of the CNS. We cover neuronal energy consumption in neural transmission and basic ('housekeeping') cellular processes and discuss the multifaceted role of non‐neuronal cells in the transport of energy substrates and in the supply and usage of different energy fuels. Finally, we address pathological consequences of disrupted energy homeostasis in the CNS. Read the Preface for the article on doi:10.1111/jnc.14836